Effects of the supernatant of Chlorella vulgaris cultivated under different culture modes on lettuce (Lactuca sativa L.) growth - Dai, Lin; Yu, Peng; Ma, Pengyao; Chen, Cheng; Ma, Jun; Zhang, Jinli; Huang, Bo; Xin, Zhikun; Zheng, Xufan; Tang, Tao (Frontiers in Nutrition, 2024)
CO2 capture by microalgae is a feasible strategy to reduce CO2 emissions. However, large amounts of cell-free supernatant will be produced after microalgal harvesting, which may be harmful to the environment if it is disorderly discharged. In this study, Chlorella vulgaris (C. vulgaris) was cultivated under three common cultivation modes (autotrophic culture (AC), heterotrophic culture (HC) and mixotrophic culture (MC)), and the obtained supernatant was used as fertilizer to investigate its effect on the growth of lettuce. The biomass concentration of C. vulgaris cultivated under MC and HC was 3.25 and 2.59 times that of under AC, respectively. The